Feasibility and safety of a rapid-access transient ischemic attack clinic. Issue 3 (7th March 2022) - Hermanson, Sarah; Vora, Nirali; Blackmore, C. Craig; Williams, Barbara; Isenberg, Nancy
ABSTRACT: Background: In the United States, patients with transient ischemic attacks (TIAs) are commonly admitted to the hospital despite evidence that low-risk TIA patients achieve improved outcomes at lower costs at specialized rapid-access TIA clinics (RATCs). Local problem: All patients experiencing TIAs at a hospital system in the Pacific Northwest were being admitted to the hospital. This project aimed to implement an RATC to relocate care for low-risk TIA patients, showing feasibility and safety. Methods: Following implementation of the RATC, a retrospective chart review was performed. Outcomes included days to RATC; days to magnetic resonance imaging (MRI); final diagnosis; stroke-related admissions and deaths within 90 days of the RATC visit. Interventions: From 2016 to 2018, implementation of an RATC included patient triage tools; multidisciplinary collaboration between departments; a direct scheduling pathway; and emphasis on stroke prevention. Results: Ninety-nine patients were evaluated in the RATC, 69% (69/99) were referred from the emergency department. Sixty-six percent of patients were seen in the TIA clinic in 2 days or less, 19% at 3 days, and 15% at 4 days or more. Mean days to TIA clinic was 2.5 days (SD 2.4). Mean days (SD) to MRI was 2.1 days (SD 2.3). Forty-eight percent (48/99) had a final diagnosis of probable TIA, followed by 32% (32/99) who had other diagnoses; 15% (15/99) migraine variant; 4% (4/99) with stroke. Two percent (2/99) of patients had a stroke-related admission within 90 days, another 2% (2/99) died of non–stroke-related causes within 90 days of the RATC visit. Conclusions: Utilization of RATCs is feasible and safe. Nurse practitioners are integral in delivering this innovative, cost-effective model of care.